The Impact of the Zakat Calculator Application on Zakat and Waqf Management Study Program Students - Andi Harpepen; Yuyun Yuniara; Mitra Ningsih Safitri; Muhammad Pebri Yanto (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Regarding the zakat calculator application using a programming language that can be used for smartphones/mobile phones with a simple program appearance according to the type of zakat you want to calculate so that it can be used by students. This application makes it easier for people, especially students, to carry out zakat calculation activities according to their types. From the system that has been implemented, the results of calculating zakat according to its type will be easier because the system used is a practical system in the form of a smartphone/cell phone application that can be easily accessed and the results can be accepted by the community, especially students. The zakat calculator application is an application that is applied to an Android smartphone which can help Muslims in calculating zakat that must be issued according to the regulations of Allah and His Messenger which can be used anytime, anywhere, and by anyone, besides that this application is also equipped with a menu feature in which there is an explanation of the history of zakat, zakat law, types of zakat, and mustahik zakat. This application uses the formula for calculating zakat assets and professional zakat which is applied to a coding program that will calculate the amount of zakat assets and professional zakat that must be issued by Muslims. This zakat calculation application can help Muslims in calculating zakat assets and professional zakat that must be issued and with the zakat alarm feature it can be used as a reference for reminders in paying zakat in a timely manner.